2020
DOI: 10.3390/ijerph17093198
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Providers’ Knowledge and Attitude Towards Abortions in Thailand: A Pre-Post Evaluation of Trainings on Safe Abortion

Abstract: Although physicians in Thailand can carry out abortions legally, unsafe abortion rates remain high and have serious consequences for women’s health. Training programs for healthcare providers on the ‘Care of unplanned and adolescent pregnancies for the prevention of unsafe abortions’ have been implemented in Thailand with the aim of providing information and challenging negative attitudes about abortions. This study investigated the participants of the training courses in order to: (i) evaluate their knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…Boonthai et al reported that these three conditions were among the most important reasons for physicians to be comfortable with performing abortions [17]. A recent study by Sanitya et al also pointed in the same direction [18].…”
Section: Results Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Boonthai et al reported that these three conditions were among the most important reasons for physicians to be comfortable with performing abortions [17]. A recent study by Sanitya et al also pointed in the same direction [18].…”
Section: Results Discussionmentioning
confidence: 86%
“…Another study was carried out in. The study found that proper training in medical schools had positive impact on the attitudes to incorporate abortion practice among new medical graduates [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, findings from a recent descriptive study among healthcare providers in Thailand showed that nurses and supporting staff could be potential target groups for further training. 17 The evidence from this study indicated that following the implementation of a training program, healthcare providers' attitudes toward unplanned pregnancies and unsafe abortions became significantly more positive.…”
Section: Discussionmentioning
confidence: 75%
“…Thai Penal Code 305 and Thai Medical Council Regulation 2005 permit legal abortions for pregnant women experiencing severe stress from the risk of having a fetus with severe anomalies and/or genetic disorders as determined by a quali ed physician [3]. Safe abortions are promoted for these women and are covered by national health insurance.…”
Section: Introductionmentioning
confidence: 99%